Aktivitas Publikasi Humas Terhadap Peningkatan kinerja Anggota DPRD Kota Kendari Marwan S. Wanto, Muhammad Ihsan Mattalitti, Yunitawati Lampasa - S. Wanto, Marwan; Ihsan Mattalitti, Muhammad; Lampasa, Yunitawati (Parabela: Jurnal Ilmu Pemerintahan & Politik Lokal, 2021)
The Regional People's Representative Council (DPRD) as a legislative institution thatrepresents the aspirations of the community is always expected to run according tothe expectations of the people. Their functions and responsibilities are themanifestations of activities that must be carried out fully to fulfill the will of thepeople. Therefore, the people have the right to know the activities that have beencarried out by DPRD members when carrying out their duties during society. Thisresearch describes the publication activities carried out by Sub. The Public Relationsand Protocol Section of the Kendari City DPRD where has implications for theperformance of the members of the Kendari City DPRD. The research approach wascarried out through qualitative methods. Research data obtained from the results ofobservations, interviews, and documentation. The results of this study indicate thatthrough the activities of internal publication, external publication, and performance,it is seen that there is an impact on improving the performance of members of theKendari City DPRD. This is measured based on indicators of productivity,responsiveness, and accountability. A publication that is carried out is effective inimproving performance because it will create a positive image for DPRD Membersthat motivates them to work better